A Comparative Analysis of Photographic Metaphors in the Lyrics of "Monokrom" (Tulus) and "Photograph" (Ed Sheeran) - Revi Angel Sonata Sitorus; Febe Elnosa Kasih; Ginto Sianturi; Anggun Yuni Sarah Saragih; Halimatussakdiah Halimatussakdiah (Dinamika Bahasa dan Budaya, 2026)
This study aims to explain the comparison of the use of photographic metaphors as a means of preserving memories in the lyrics of the song "Monokrom" by Tulus and "Photograph" by Ed Sheeran using a comparative literary approach. The methodology applied is descriptive qualitative, employing content analysis as well as heuristic and hermeneutic readings to uncover the hidden meanings within the lyrics. The findings of this study indicate that both songs generally use photographic metaphors as a means to combat forgetting and slow down time to preserve emotional memories. Nevertheless, there are clear differences in the emotional functions and cultural nuances underlying the two works. In the song "Monokrom," photographic metaphors such as "black-and-white photo sheets" possess a retrospective and collective character, highlighting feelings of gratitude, appreciation, and self-reflection regarding shared life experiences with others. On the other hand, the song "Photograph" utilizes metaphors like "frozen still," which reflect a prospective and individual nature, serving as a protective mechanism to shield a romantic relationship from the threats of distance and time. This difference reflects Indonesia’s cultural background, which places greater emphasis on togetherness, in contrast to Western culture, which focuses more on personal experience. This analysis also underscores the importance of intermediality, where visual media (photographs) are translated into poetic language that provides a multisensory experience for the listener. The conclusion of this study indicates that while memory is a shared human experience, its expression through metaphors is grounded in the cultural context and emotional needs of its creators. Keywords: Comparative literature, Photography, Song lyrics, Visual memory